ISOLATION AND MOLECULAR CHARACTERISATION OF PANDEMIC A/H1N1 INFLUENZA VIRUS FROM PIGS IN AN INTENSIVE PIGGERY COMPLEX IN LAGOS, NIGERIA (2014)
Novel pandemic A/H1N1 influenza virus containing gene segments from pig, bird, and human influenza viruses was first detected in Mexico in 2009. Emergence of the virus further underscores the importance of animals in the epidemiology of influenza viruses. It is also known that intensification of livestock farming increases the potential for circulation of influenza virus at the human-animal interface but there is dearth of data on the situation in Nigeria. This study was therefore designed to characterise and determine the phylogeny of pandemic A/H1N1 influenza virus circulating in an intensive piggery complex in Lagos, Nigeria. Sentinel surveillance was carried out in a large intensive piggery at Oke Aro, Lagos State with monthly sampling for two years (2010-2012). Two hundred and twenty seven and 40 nasal swabs was respectively collected from pigs and pig handlers presenting with influenza-like illness, were analysed by Real-Time Reverse Transcriptase Polymerase Chain Reaction (RRT-PCR). Virus isolation from samples that were confirmed positive by RRT-PCR was carried out in 8-10 days old embryonated chicken eggs. Isolates were identified by RRT-PCR and haemagglutination inhibition using subtype specific primers and homologous reference antisera respectively. The virus was also visualized with an electron microscope following negative stain with 2% phosphotungstic acid. Cycle sequencing of the isolates was carried out and basic local alignment search tool was used to compare gene sequences obtained with others in the Genbank and global initiative for sharing all influenza data. Nucleotide sequence alignment and construction of phylogenetic trees of full gene segments were done using MEGA5 software and the Neighbour-Joining method with 1,000 bootstrap replicates. Data were analysed using descriptive statistics at P=0.05 Thirty one (13.7%) of the 227 specimens from pigs analysed were positive for influenza A matrix gene by RRT-PCR while none of the 40 specimens from pig handlers was positive for influenza A virus. Twenty nine (12.8%) isolates were obtained from the samples out of which 18 (7.9%) were subtyped as pandemic A/H1N1 influenza virus. The haemagglutinin and neuraminidase genes of representative isolate A/swine/Nigeria/12VIR4047/2011 with Genbank accession numbers JX442481 and JX442482 showed 99% homology with pandemic A/H1N1 influenza virus earlier isolated from human in San Diego, Cameroon, Ghana and Nigeria. However there were 13 nucleotides and 3 amino acid substitutions in the haemagglutinin gene compared with similar viruses and the prototype A/California/07/2009 especially aspartate to arginine mutation at antigenic binding site 240 position (H1-numbering) on the haemagglutinin gene. All the internal genes clustered with global 2009 pandemic influenza A/H1N1 virus on the phylogenetic tree but were more related to human isolates. This study showed for the first time, isolation and some molecular properties of pandemic A/H1N1 influenza virus circulating in Nigeria. The observed mutations have implications on the transmissibility and pathogenicity of the virus in different hosts. Surveillance and control measures incorporating human and veterinary components are recommended since uninterrupted circulation of the virus in pigs may lead to reassortment in the animal host and emergence of novel subtypes with more severe consequences to human and animal populations